2016
DOI: 10.1016/j.tetasy.2016.08.013
|View full text |Cite
|
Sign up to set email alerts
|

2-Azanorbornane-based amine organocatalyst for enantioselective aldol reaction of isatins with ketones

Abstract: Optically active 2-azanorbornane-based organocatalysts were designed and synthesized, and the catalytic activity of these catalysts in enantioselective aldol reactions of isatins with ketones was investigated. Among these catalysts, 2-azanorbornylmethanol showed the best catalytic activity to afford the corresponding aldol product in excellent chemical yield (up to 95%) and with moderate stereoselectivity (up to 64% ee, up to syn:anti = 36: 64).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Our study commenced with the examination of the catalytic activities of the simple amino alcohols 11a – 11d , 12a – 12e , and 13 with one covalent and one noncovalent binding site along with one sterically hindered site. [11d] We initially attempted the crossed aldol reaction of 1a with 2 with catalyst 11a as a chiral inducer and benzoic acid and water as additives in tetrahydrofuran (THF) to afford the aldol product. As the obtained product was unstable, it was isolated in low chemical yield and poor enantioselectivity as diol 5a after reduction with NaBH 4 (Table , Entry 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study commenced with the examination of the catalytic activities of the simple amino alcohols 11a – 11d , 12a – 12e , and 13 with one covalent and one noncovalent binding site along with one sterically hindered site. [11d] We initially attempted the crossed aldol reaction of 1a with 2 with catalyst 11a as a chiral inducer and benzoic acid and water as additives in tetrahydrofuran (THF) to afford the aldol product. As the obtained product was unstable, it was isolated in low chemical yield and poor enantioselectivity as diol 5a after reduction with NaBH 4 (Table , Entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have explored simple primary amino alcohols as a new class of organocatalysts with distinctive properties such as easy synthesis, stability to air, potential for convenient alteration of the steric sites, and ability to be used as bifunctional (enamine activation and noncovalent activation) catalysts , . The design and synthesis of new organocatalysts is always an important and challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…2-Azanorbornane (2-azabicyclo [2.2.1]heptane) and other 2-azabicycloalkanes with a chiral bicyclic backbone can be used as a versatile platform for the preparation of compounds exhibiting interesting biological activity, and a variety of heterocyclic compounds that have already found application in asymmetric synthesis as ligands or organocatalysts [ 14 ]. As an example, a series of derivatives of 2-azanorbornane prepared by Nakano and co-workers ( Figure 1 ) were applied in a stereoselective reaction of isatins with ketones [ 15 ]. A catalyst bearing a hydroxyl group led to aldol products in high yields (up to 95%) and modest stereoselectivity ( syn:anti up to 36:64, up to 64% ee ).…”
Section: Introductionmentioning
confidence: 99%
“…Efficient covalent and non‐covalent organocatalysts have been explored for proceeding successfully a wide range of reactions . 2‐Azanorbornane A having cage structure is prepared by the hetero Diels‐Alder (HDA) reaction of cyclopentadiene with chiral imino dienophile, and the cage compound works as useful synthetic intermediate for converting to various biologically active compounds such as anti‐tumor drugs (Scheme ) . 2‐Azanorbornane‐based amino alcohol B , that is derived from the DA adduct A , has bulky 2‐azanorbornane backbone and the cage structure contains nitrogen atom acting as a Brønsted basic site.…”
Section: Introductionmentioning
confidence: 99%
“…However, till now only a few successful studies were reported by using the compound B containing with di ‐phenylmethanol moiety at 3‐position and thiourea derived azanorbornanes as organocatalyst for asymmetric aldol and Michael reactions respectively. [2a], [2e] Especially, to the best of our knowledge, the successfully use of 2‐azanorbornanes B with mono ‐phenylmethanol moiety at 3‐position as organocatalyst has not been reported until now.…”
Section: Introductionmentioning
confidence: 99%